XVII Congress of the International Organization for Septuagint and Cognate Studies : Aberdeen, 2019 - Kotzé, Gideon R.; Meer, Michaël N. van der; Rösel, Martin (Septuagint and cognate studies series ;, 2022)
"This volume from the International Organization for Septuagint and Cognate Studies (IOSCS) includes the papers given at the XVII Congress of the IOSCS, which was held in Aberdeen in 2019. Essays in the collection fall into five areas of focus: textual history, historical context, syntax and semantics, exegesis and theology, and commentary. Scholars and students of the translation, theology, and reception of the Old Greek translation of Scripture will find in this volume critical information for future work in Septuagint studies"--